1997
DOI: 10.1038/bjc.1997.505
|View full text |Cite
|
Sign up to set email alerts
|

Vascular endothelial growth factor and lymph node metastasis in primary lung cancer

Abstract: Summary The relationship between vascular endothelial growth factor (VEGF) and lymph node metastasis was studied in 90 cases of primary lung cancer without distant metastasis. As a result of quantitative reverse transcription polymerase chain reaction (RT-PCR) analysis, the VEGF121 mRNA expression levels in lung cancer tissues with nodal metastasis (n = 35) were higher than in those without nodal metastasis (n = 55). However, no significant difference could be found in VEGF121 mRNA expression levels as stratif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

9
47
3
1

Year Published

1999
1999
2003
2003

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 75 publications
(60 citation statements)
references
References 14 publications
9
47
3
1
Order By: Relevance
“…The pattern of VEGF is that VEGF expression of Group N(+) is much greater than that of Group N(-); however, the expression of VEGF is suppressed with the progression of metastatic stage. We and other investigators showed that over-expression of VEGF in primary tumours correlates with lymph node metastasis in oesophageal cancer and other tumours (Maeda et al, 1996;Moriyama et al, 1997;Ohta et al, 1997;Uchida et al, 1998). VEGF is a multifunctional molecule that has been implicated in vasculogenesis (Carmeliet et al, 1996;Ferrara et al, 1996), endothelial cell proliferation and migration (Senger et al, 1993), vascular permeability (Roberts and Palade, 1995), and stromal degradation through the activation of some proteolytic enzymes involved in tumour invasiveness and angiogenesis (Ferrara, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…The pattern of VEGF is that VEGF expression of Group N(+) is much greater than that of Group N(-); however, the expression of VEGF is suppressed with the progression of metastatic stage. We and other investigators showed that over-expression of VEGF in primary tumours correlates with lymph node metastasis in oesophageal cancer and other tumours (Maeda et al, 1996;Moriyama et al, 1997;Ohta et al, 1997;Uchida et al, 1998). VEGF is a multifunctional molecule that has been implicated in vasculogenesis (Carmeliet et al, 1996;Ferrara et al, 1996), endothelial cell proliferation and migration (Senger et al, 1993), vascular permeability (Roberts and Palade, 1995), and stromal degradation through the activation of some proteolytic enzymes involved in tumour invasiveness and angiogenesis (Ferrara, 1996).…”
Section: Discussionmentioning
confidence: 89%
“…Several reports indicated that expression of VEGF in tumor tissue of NSCLC significantly correlated with lymph node metastasis, tumor size, and advanced stage [10,15,16]. In terms of serum VEGF, Imoto et al [15] demonstrated that the elevated preoperative serum VEGF levels of patients who underwent complete tumor resection were significantly associated with advanced stage, suggesting the role of serum VEGF as an indicator of tumor burden.…”
Section: Discussionmentioning
confidence: 99%
“…It is a soluble dimeric 34-46 kDa protein which has been implicated in endothelial cell proliferation and migration, increased vascular permeability, and stromal degradation through the activation of proteolytic enzymes [2,[4][5][6]. VEGF expression has been demonstrated in a large variety of human malignancies including breast, lung, colorectal, bladder, and ovarian cancer [2,[6][7][8][9][10][11][12][13][14][15][16]. In non-small cell lung cancer (NSCLC), expression of VEGF has been reported in 50-95% of cases [8-10,12,14 -16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is therefore important to be able to assess VEGF gene product expression in tumor cells in order to understand the role of VEGF in tumor angiogenesis and in the biological behavior of tumors. Many studies of VEGF expression in various malignancies have been performed in recent years (Berkman et al, 1993;Boocock et, 1995;Fontanini et al, 1997;Ohta et al, 1996Ohta et al, , 1997Oshika et al, 1994;Suzuki et al, 1996;Tokunaga et al, 1998;Viglietto et al, 1996).…”
Section: Discussionmentioning
confidence: 99%